2019
DOI: 10.1016/j.energy.2019.05.137
|View full text |Cite
|
Sign up to set email alerts
|

Exergy return on exergy investment analysis of natural-polymer (Guar-Arabic gum) enhanced oil recovery process

Abstract: This paper probes the transport of CO 2 soluble surfactant for foaming in porous media. We numerically investigate the effect of surfactant partitioning between the aqueous phase and the gaseous phase on foam transport for subsurface applications when the surfactant is injected in the CO 2 phase. A 2-D reservoir simulation is developed to quantify the effect of surfactant partition coefficient on the displacement conformance and CO 2 sweep efficiency. A texture-implicit local-equilibrium foam model is embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 83 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…This viscoelastic behaviour is attributed by the formation of wormlike micelles (WLMs) [28]. In addition, smart wormlike micelles (WLMs) or smart self-organized structures, can be used in a myriad of applications within the oil and gas industry, including hydraulic fracturing, emulsions, polymer, surfactant, and foam flooding [15,32]. Nowadays, investigation is carried out to develop WLMs that respond to external stimuli for the ease to control visco-elasticity [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This viscoelastic behaviour is attributed by the formation of wormlike micelles (WLMs) [28]. In addition, smart wormlike micelles (WLMs) or smart self-organized structures, can be used in a myriad of applications within the oil and gas industry, including hydraulic fracturing, emulsions, polymer, surfactant, and foam flooding [15,32]. Nowadays, investigation is carried out to develop WLMs that respond to external stimuli for the ease to control visco-elasticity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 , 14 ]. At an early stage of hydraulic fracturing, polymer fluids such as guar gum [ 15 , 16 ] was used mostly as a thickening agent for the fracturing fluid [ 17 , 18 ]. Laboratory experiments have shown that traditional polymer-based fluids generate residue(s), which can damage the formation and reduce the pore conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…and production wells. The practical pumping exergy is calculated by including the mechanical efficiency of the pump (80%), efficiency of the electrical driver (90%), and the efficiency of the power plant (50%), which gives overall efficiency of 36% for the pumps (Eftekhari et al, 2012;Hassan et al, 2019):…”
Section: Tablementioning
confidence: 99%
“…The exergy analysis considers the exergy inputs and exergy "wastes". The proposed approach is similar to the energy return ratio (ERR) or energy return on investment (ERoEI) concept, that has been used to measure the "energetic productivity" of the oil industry (Brandt et al, 2015;Hassan et al, 2019). The ERR is the ratio between the energy provided and the energy consumed (Hassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation